Sur la composition des séries de Dirichlet avec les exposants complexes - Popov, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:B. П. Попов. О композиции рядов Дирихле с комплексными показателямиV. Popovas. Dirichle eilučių su kompleksiniais rodikliais kompozicijos klausimu